Pengaruh Profitabilitas, Ukuran Perusahaan dan Leverage Terhadap Manajemen Laba Pada Perusahaan BUMN Manufaktur Yang Terdaftar di BEI Tahun 2018-2021 - Asyfa Lutfiyah (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2023)
The purpose of this study to exmine how profitability, firm size, and leverage of manufacturing BUMN companies listed on the Indonesian Stock Exchange from 2018 to 2021 affect revenue management. The sample for this study was eight companies using a saturated sampling technique. We selected the samples so that we had as many as 32 samples of data. The data used are secondary data from annual reports of samples companies. The data analysis technique uses multiple linear regression analysis powered by IBM SPSS version 25 software.the results show that profitability has a great influence on profit management partly with probability value = 0.002 0.05, while firm size has a great influence on profit management partly with probability value = 0.013 0.05. indicating that leverage does not significantly affect profits. Control in probability = 0.016 0.05. we simultaneously show that the variables profitability, firm size, and leverage all have a significant impact on revenue management when prob = 0.000 alpha = 0.05.